Analisis Isi Pesan Dakwah tentang Wasilah Menurut K.H. Ahmad Bahauddin Nursalim di Instagram: Content Analysis of the Preaching Message about Wasilah According to K.H. Ahmad Bahauddin Nursalim on Instagram - Muhammad Lukman Hakim (PROGRESIF: Jurnal Dakwah, Sosial, dan Komunikasi, 2025)
Social media, particularly Instagram, has become an effective medium for conveying Islamic preaching messages (da’wah). This study aims to analyze the content of wasilah-themed da’wah messages delivered by K.H. Ahmad Bahauddin Nursalim (Gus Baha) and to examine their impact on the development of Islamic preaching through Instagram. The research employs a content analysis method with a cultural approach, using data collected from the Instagram accounts @kajian.gusbaha, @ulama_ndonesia, @gusbaha1menit_official, and @shorts_gusbaha. Data were gathered through non-participant observation and literature study, and analyzed using the Miles and Huberman interactive model. The findings indicate that the da’wah messages are categorized into three types: wasilah through figures (individuals), wasilah through worship practices, and wasilah through supplications and dhikr. These contents have a positive influence by motivating, inspiring, and strengthening the spiritual enthusiasm of Muslim communities, especially the younger generation. This study demonstrates the strategic role of digital da’wah via Instagram in promoting accessible and engaging Islamic teachings.